2021
DOI: 10.20527/ilung.v1i2.4114
|View full text |Cite
|
Sign up to set email alerts
|

PKM Introduksi Sediaan Konsentrat Hijauan Rawa Sebagai Sumber Protein Itik Alabio

Abstract: Duck feed ingredients are currently still expensive and less affordable for breeders, it is necessary to have alternative quality feed ingredients originating from potential superior swamp plants. The activity aims to provide concentrate preparations from swamp forage as feed ingredients for ducks to reduce feed prices, improve ration quality and income (IOFC) for laying ducks. The activity partner is the Keraton duck group in the Martapura sub-district, Banjar Regency. The activity lasts months. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…Furthermore, the usage of herbal medicines is inexpensive and easy to obtain and produce by farmers themselves. In addition, the usage of herbal medications is inexpensive and easy to obtain and produce by farmers themselves [4,5,11]. According to [14], herbal medicine has been shown to boost chicken immune systems and can be used as an antidote and preventative measure for hazardous infectious diseases.…”
Section: Impact Of Herbal Medicine On Duck Mortalitymentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the usage of herbal medicines is inexpensive and easy to obtain and produce by farmers themselves. In addition, the usage of herbal medications is inexpensive and easy to obtain and produce by farmers themselves [4,5,11]. According to [14], herbal medicine has been shown to boost chicken immune systems and can be used as an antidote and preventative measure for hazardous infectious diseases.…”
Section: Impact Of Herbal Medicine On Duck Mortalitymentioning
confidence: 99%
“…The dose of herbal medicine administered in drinking water was as much as 2 ml / week / head and was quite effective. According to [11] that the administration of herbal Phyto biotics at a 2% ration dose generated the best results for the parameters of final body weight, average daily weight gain (ADG), and FCR in male Alabio ducks up to six weeks of age. [20] found that the best dose level of herbal medicine to produce broiler duck carcasses was 9 cc / head / day, with a higher body weight than other treatments, and a business scale of 140 heads yielded a profit of IDR 2,150,000 / maintenance period, with an R/C of 1.35.…”
Section: Fig 1 Percentage Of Mortality Loss and Rejected Ducksmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Biyatmoko etl al. [16] the use of herbal phytobiotics with a combination of several herbal plants such as turmeric, ginger, garlic, kencur, galangal, temulawak, cinnamon and fermented betel leaf mixed into alabio duck feed to a level of 2% showed the best results for body weight final, weight gain and ration conversion. Research on the administration of jamblang to replace of antibiotics, especially for broilers, is very minimum.…”
Section: Introductionmentioning
confidence: 99%